Analysis of Security Management for Passenger Services at the Tanjung Priok Port Passenger Terminal - Suparman Suparman; Roy Kasiono; Sugiyanto Sugiyanto; Roma Dormawaty; Mochamad Ely Ridwan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This research is motivated by the strategic role of Tanjung Priok Port as a national economic gateway that faces complex security challenges, especially during peak passenger traffic periods. The purpose of this study is to analyze the relationship and influence of security management on passenger service and to formulate service optimization strategies. The method used is a mixed method approach with a sequential explanatory design, which integrates quantitative data from 100 respondents via questionnaires with qualitative data from in-depth interviews and field observations. The results show a strong positive relationship (r=0.780) between security management and passenger service, with a contribution of 60.8%. However, the qualitative analysis reveals a decoupling phenomenon where the implementation of SOPs becomes situational during times of surge in operations to avoid queues, and the paradigm of officers who are still militaristic, which reduces passenger psychological comfort. The study concludes that physical security assurance does not automatically increase satisfaction if it is not accompanied by dimensions of empathy and friendly service. These findings imply the importance of transforming human resource competencies towards hospitality-based security and structuring technological infrastructure to create a balance between international security standards and excellent service.